The Impact of the Covid-19 Pandemic on Stock Investment in the Indonesian Capital Market - Maulana Majied Sumatrani Saragih; Sarman Sinaga; Faisal Faisal; Rico Nur Ilham; T Nurhaida (Management Research and Behavior Journal, 2021)
The COVID-19 pandemic has hit various sectors, including the stock market where many people are hesitant to invest in stocks. Many industries have been affected by Covid-19, where since March 2020 the Indonesia Stock Exchange Composite Stock Price Index (IHSG) has decreased because many investors sold their shares, but since the third week of May 2020 to early June 2020 has shown an increase indicating stock trading has begun to show improvement. This study aims to analyze which sector stocks are still able to survive during the COVID-19 pandemic, by using stock trading volume data, Composite Stock Price Index (IHSG), weekly and monthly market capitalization values with a sample of 20 stocks - the highest stocks. based on sales volume and transaction value on the Indonesian stock exchange for the period March 2020 to June 2020 obtained from the Financial Services Authority (OJK) weekly report and the Indonesia Stock Exchange (IDX) Monthly Report. The results show that during the COVID-19 pandemic, investors can still get benefits in investing in stocks if every decision made by these investors is supported by careful calculations.